Recent advances in high-entropy superconductors - Lingyong Zeng; Longfu Li; Kuan Li; Rui Chen; Huixia Luo (NPG Asia Materials)
Abstract High-entropy materials (HEMs) exhibit significant potential for diverse applications owing to their tunable properties, which can be precisely engineered through the selection of specific elements and the modification of stoichiometric ratios. The discovery of superconductivity in HEMs has garnered considerable interest, leading to accelerated advancements in this field in recent years. This review provides an overview of various high-entropy superconductors, highlighting their distinct features, such as disordered crystal structure, factors affecting the critical temperature (T c), unconventional superconductivity, and topological bands. A perspective on this field is subsequently proposed, drawing upon insights from recently published academic literature. The objective is to provide researchers with a comprehensive and clear understanding of the newly developed high-entropy superconductivity, thereby catalyzing further advancements in this domain.